Effect and Safety of Mycophenolate Mofetil or Sodium in Systemic Sclerosis-Associated Interstitial Lung Disease: A Meta-Analysis - Argyris Tzouvelekis; Nikolaos Galanopoulos; Evangelos Bouros; George Kolios; George Zacharis; Paschalis Ntolios; Andreas Koulelidis; Anastasia Oikonomou; Demosthenes Bouros (Pulmonary Medicine)
Background. Interstitial lung disease (ILD) is the most common complication of systemic sclerosis (SSc) with treatment ineffective. Objective: The aim of this meta-analysis was to provide an estimate of the safety and efficacy profile of Mycophenolate Mofetil (MMF) or sodium (MMS) in SSc-ILD patients. Materials and Methods. All studies were reviewed systematically. The main end-points were safety and efficacy profile as estimated by forced vital capacity (FVC)% and diffusion capacity of the lung for carbon monoxide (DLCO)% of the predicted normal value (%pred.) before and after treatment in patients with SSc-ILD. Quality assessment and data extraction were performed independently by two reviewers. Results. Seventeen studies were reviewed systematically. Six studies, one prospective, were eligible for analysis encompassing 69 patients, including 10 subjects from our, yet unpublished, retrospective study. There was no statistically significant difference in both efficacy outcomes of interest, including FVC% pred. (weighted mean difference 1.48, 95% confidence interval (CI): −2.77 to 5.72, P=0.49) and DLCO % pred. (weighted mean difference −0.83, 95% CI: −4.75 to 3.09, P=0.93). No cases of clinically significant side effects were documented. Conclusions. Meta-analysis data suggest that MMF is a safe therapeutic modality which was associated with functional stabilization in patients with SSc-ILD.